THE QUR'AN AND TIME MANAGEMENT - Amaruddin, Amaruddin (SYAHADAH : Jurnal Ilmu al-Qur'an dan Keislaman, 2024)
Time is one of the elements that runs parallel with human life. Furthermore, time is something that does not provide a second chance for a person’s life, but it does offer an opportunity to plan something, by managing the time one has. Time management, or often referred to as time control, is an issue that is often overlooked. Time management is a method or way for someone to design and plan something regarding the time they have, so that it can be used optimally. The Qur'an, as guidance for humanity, also commands to practice time management. This can be found in Surah Al-Ashr and Surah An-Naba verses 9-11. Surah Al-Ashr elaborates on the command to manage the time one possesses, while Surah An-Naba verses 9-11 explains how to utilize time optimally in daily life.